Characterisation of Soils in Relation to Site Index of Eucalyptus Tereticornis - Samra, J. S.; Singhal, R. M.; Sharma, S. D. (Indian Forester, 1985)
Variation in site index (S.I.) of 4-13 year old Eucalyptus plantations have been discussed in relation to physico-chemical characteristics of soil of Tarai Central Forest Division. S.I. ranged from 15.2 to 25.8 metres at an index age of 8 years. S.I. was generally higher in Aquolls and Udolls of lower peidmonts (Tarai) where soil characteristics associated with excessive wetness were observed. However, high pH due to distribution of CaCO3 throughout the profile affected site index adversely. Growth of Eucalyptus was the lowest in skeletal Haplustolls of upper peidmont (Bhabar) because of the presence of gravels and pebbles. Sandy texture of non-skeletal Haplustolls also seem to have lowered the S.I. in the transition zone between upper (Bhabar) and lower (Tarai) peidmonts. Roots were crinckled, twisted and bunchy in appearance indicating restricted distribution in skeletal soils.